Renovating the Roman Colosseum: Politics, urban restructuring, and the value of heritage in neoliberal times. Issue 3 (3rd July 2019) - Galbo, Joseph
ABSTRACT: The paper presents debates over two renovations of the Roman Colosseum between 2011 and 2015, within a broader historical and political context, as prisms through which we can explore the entanglements of neoliberal politics, urban restructuring, and the ways in which heritage is being valued. With reference to the criticisms of art historian Tomaso Montanari, archaeologist Salvatore Settis, and anthropologist Michael Herzfeld, the current study examines the political, aesthetic, and ethical rationalities inscribed in the renovations of the Colosseum and the spatial organisation of the city more generally. The paper concludes by outlining how new forms of political populism in Italy, feeding on the discontents of neoliberalism, have placed heritage at the centre of intensely contested questions of citizenship and national identity.